Brexit and its Implications for the UK International Investment and Trade Agreements - D. K. Labin; V. S. Retyunskiy (Московский журнал международного права)
The paper discusses the legal implications of the 2016 decision to withdraw Britain from the European Union. The authors explore the international legal aspects of the procedures of a British exit from the EU. In this regard the authors analyze article 50 of the 2007 Lisbon Treaty. Special attention is paid to the study of the legal implications of the UK investment and trade agreements. In particular, the authors go into detail about the future of intra and extra-EU BITs as well as UK trade agreements. The paper also contains some points of the Plan for Britain set out by Prime Minister Theresa May, which include the top priorities that the UK government will use to negotiate Brexit. In conclusion, the authors predict the most probable scenarios for the “post-brexit” relations between the UK and the EU. Possible negociation outcomes are as follows. The UK could remain part of the European Economic Area and have a relationship with the EU like Norway, Iceland and Lichtenstein. The UK could seek to negotiate a comprehensive free trade agreement with the EU as Canada and South Korea have done. The purest form of “out” requiring no formal connections or negotiated agreement is WTO-only relationship.